2010
DOI: 10.1292/jvms.09-0411
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Recombinant Relaxin on In Vitro Maturation of Porcine Oocytes

Abstract: ABSTRACT. Relaxin, a member of the insulin superfamily, has diverse functions in both reproductive and nonreproductive tissues. The aim of the present study was to evaluate the effects of recombinant relaxin on the in vitro maturation of porcine oocytes and their subsequent embryonic development following in vitro fertilization. Three concentrations of relaxin (1, 10, and 100 ng/ml) were used in the in vitro maturation (IVM) medium [TCM supplemented with 10% (v/v) porcine follicular fluid, 10 ng/ml of epiderma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The existence of such interactions may also explain our contradictory results with a recent study reporting a lack of relaxin effect on nuclear maturation of pig oocytes [39]. These authors tested the effect of recombinant human relaxin added in maturation medium already containing porcine follicular fluid (10%) and whose high relaxin contents [8,40] and beneficial effect on oocyte maturation [41,42] could have interfered with their results.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The existence of such interactions may also explain our contradictory results with a recent study reporting a lack of relaxin effect on nuclear maturation of pig oocytes [39]. These authors tested the effect of recombinant human relaxin added in maturation medium already containing porcine follicular fluid (10%) and whose high relaxin contents [8,40] and beneficial effect on oocyte maturation [41,42] could have interfered with their results.…”
Section: Discussionmentioning
confidence: 87%
“…A recent study has demonstrated a positive effect of relaxin on glutathione (GSH) synthesis in in vitro matured porcine oocytes [39]. Indeed, GSH is a routine indicator or oocyte cytoplasmic maturation [43], whose beneficial effects on blastocyst formation and quality (hatching and cell number) are well-documented [44-48].…”
Section: Discussionmentioning
confidence: 99%
“…The addition of oestrus serum also supported high maturation rates in IVM of ewe oocytes (Rao et al, 2002;Succu et al, 2007). In addition, the research into supplementing recombinant hormones such as leptin, insulin-like growth factor, and vascular endothelial growth factor in IVM system has served to improve development of in vitro maturation in several species (Moreira et al, 2002;Boelhauve et al, 2005;Cao et al, 2009;Kim et al, 2010). However, developmental competence of in vitro matured oocytes from prepubertal animals has been reported to be lower than oocytes derived from adult animals (Pinyopummintr & Bavister, 1995;O'Brien et al, 1996;Ledda et al, 1997;Gandolfi et al, 2000;Leoni et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…However, developmental competence of in vitro matured oocytes from prepubertal animals has been reported to be lower than oocytes derived from adult animals (Pinyopummintr & Bavister, 1995;O'Brien et al, 1996;Ledda et al, 1997;Gandolfi et al, 2000;Leoni et al, 2007). In addition, the researches supplementing recombinant hormones such as leptin, insulin-like growth factor, and vascular endothelial growth factor in IVM system have been used to improve development of in vitro maturation in several species (Moreira et al, 2002;Boelhauve et al, 2005;Cao et al, 2009;Kim et al, 2010). In addition, the research into supplementing recombinant hormones such as leptin, insulin-like growth factor, and vascular endothelial growth factor in IVM system has served to improve development of in vitro maturation in several species (Moreira et al, 2002;Boelhauve et al, 2005;Cao et al, 2009;Kim et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Within the ovary, RXFP1 relaxin receptors have been identified at the transcript or protein level on granulosa and cumulus cells of pig antral follicles (Feugang et al, 2011a), and possibly also on oocytes themselves (Feugang et al, 2011b). Moreover, treatment with relaxin of porcine cumulus-oocyte-complexes in vitro, whilst appearing to have little effect on oocyte maturation, did appear to positively influence the resulting embryos (Feugang et al, 2011a;Kim et al, 2010). RXFP1 is also expressed within the corpus luteum of monkeys and cats (Braun et al, 2012;Maseelall et al, 2009), though the precise cellular localization in these tissues has not been ascertained.…”
Section: Relaxin and Ovarian Functionmentioning
confidence: 99%